Analisis Tekno Ekonomi Industri Kecil untuk Akses ke Lembaga Perbankan (Studi Kasus Pada Perusahaan Kecap Damai di Purwokerto) - Bambang Sumpeno; Rizal Syarief; Nora H Pandjaitan (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2008)
In 1997 Indonesia experienced an economic crisis which is started with the decrease in value of Rupiah towards the US Dollar. Many industries were closed, but a lot of small and medium scale industries survived and still exist until now. One of them is “Damai” kecap industry in Purwokerto. For most of small and medium scale industries, the limited capital is one of the problems to developing their business. There were several requirements to gain access to banking services, such as current ratio (CR), debt equity ratio (DER) and value of warranty. To establish a kecap industry a working capital of Rp. 62.099.500,- is needed to fulfill a one-month operational cost. Fixed assets require approximately Rp. 211.350.000,- (excluding land), so the total capital needed is Rp. 273.449. 500,-. The marketing analysis shows that the break-even point (BEP) of the kecap industry is 14.625 bottles or approximately Rp. 68.471.671,-, and CR is 165,90%. It means that the kecap industry should be able (liquid) to settle current liabilities from its current assets. The banks ask for a minimum current ratio of 120,00%. DER of this kecap industry is 20,45%, which means that the kecap industry has enough capital to settle its liabilities. The banks ask for maximum DER of 200,00%. In order to enlarge its business, the industry needs to increase its capacity. It means that “Damai” kecap Industry needs an extra credit from bank or kecap industry can cooperate with the third party as investor. An industry needs a lot of time to gain credit from a bank. The “Damai” kecap Industry can obtain extra credit of Rp. 100.000.000,- from its land and building because their value is more than Rp. 400.000.000,-.